2016
DOI: 10.1016/j.ajic.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Clostridium difficile infection (CDI) incidence as a risk factor for hospital-associated CDI

Abstract: Background Environmental risk factors for Clostridium difficile infections (CDIs) have been described at the room or unit level but not the hospital level. To understand the environmental risk factors for CDI, we investigated the association between institutional- and individual-level CDI. Methods We performed a retrospective cohort study using the Healthcare Cost and Utilization Project state inpatient databases for California (2005–2011). For each patient’s hospital stay, we calculated the hospital CDI inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 36 publications
(31 reference statements)
0
25
0
Order By: Relevance
“…All of these hospital-level risk factors confirm previous findings at the individual level. 8,[14][15][16][17][18]27 Our method of estimating the burden of disease attributable to hospital transfers used a statistical model and a counterfactual-like approach. This approach was based on conditional expectations; we compared the expected number of CDI cases given that there is a network effect versus the expected number of CDI cases given that the network effect is negated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these hospital-level risk factors confirm previous findings at the individual level. 8,[14][15][16][17][18]27 Our method of estimating the burden of disease attributable to hospital transfers used a statistical model and a counterfactual-like approach. This approach was based on conditional expectations; we compared the expected number of CDI cases given that there is a network effect versus the expected number of CDI cases given that the network effect is negated.…”
Section: Discussionmentioning
confidence: 99%
“…24 Higher risks of CDI have also been reported in rooms where a previous occupant had a CDI 25,26 and in hospitals with higher CDI incidence. 27 The increased risk associated with environmental exposures could reflect a contaminated environment [25][26][27][28] or exposure to increased levels of antimicrobials beyond individual exposures. 29 Recent work has shown that hospital transfer rates have also been associated with CDI.…”
mentioning
confidence: 99%
“…To our knowledge, this is the first study to estimate the impact of CDI environmental pressure on subsequent risk of HA-CDI after accounting for both antimicrobial use and antimicrobial stewardship activities [ 34 38 ]. In this study, CDI environmental pressure was defined as the ward-level prevalence of total CDI cases (both HA-CDI and CA-CDI) and CA-CDI cases in the preceding month and current month, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In general, CDI pressure, the increasing risk of CDI acquisition with increasing numbers of CDI patients, has been documented at both the ward 11 and hospital levels. 12 More specifically, evidence for underlying environmental CDI contamination include reports of C. difficile spores on high-touch surfaces in healthcare settings, 13,14 patient skin, 15,16 and hands of healthcare workers. 17,18 In addition, C. difficile contamination increases in rooms occupied by patients with symptomatic CDI; thus, room assignments (eg, patients placed in a room with previous occupant who had CDI) are also associated with increased risk of CDI acquisition.…”
mentioning
confidence: 99%